Integrated Cost and Schedule Control Systems for Nuclear Power Plant Construction: Leveraging Strategic Advantages to Owners and EPC Firms - Youngsoo Jung; Byeong-Suk Moon; Yun-Myung Kim; Woojoong Kim (Science and Technology of Nuclear Installations)
As the owners expect that the cost and time for nuclear power plant construction would decrease with new entrants into the market, there will be severer competition in the nuclear industry. In order to achieve performance improvement and to attain competitive advantages under the globalized competition, practitioners and researchers in the nuclear industry have recently exerted efforts to develop an advanced and efficient management methodology for the nuclear mega-projects. Among several candidates, integrated cost and schedule control system is of great concern because it can effectively manage the three most important project performances including cost, time, and quality. In this context, the purpose of this paper is to develop a project numbering system (PNS) of integrated cost and schedule control system for nuclear power plant construction. Distinct attributes of nuclear power plant construction were investigated first in order to identify influencing variables that characterize real-world implementation of advanced cost and schedule controls. A scenario was then developed and analysed to simulate a case-project. By using this case-project, proposed management requirements, management methods, measurement techniques, data structure, and data collection methods for integrated cost and schedule PNS were illustrated. Finally, findings and implications are outlined, and recommendations for further research are presented.